Regulation of peel development and control of fruit cracking by gibberellin acid in Zaomi Ponkan - LIU Xin; PENG Miao; JIA Yushi; ZHAO Yushuang; CHEN Tong; WU Hailing; CHEN Yuewen; JIN Yan; LU Xiaopeng; YANG Junfeng (Guoshu xuebao)
[Objective] Gibberellic acid (GA3), a plant hormone, can affect the growth and development of plants by promoting cell division and elongation. Fruit cracking is one of the major problems leading to decreased yield and quality in Ponkan (Citrus reticulata Blanco) production. The application of GA3 has been found to effectively enhance the toughness and thickness of the fruit peel, preventing fruit cracking. This study focused on Zaomi Ponkan to investigate the impact of different concentrations of GA3 applied at the cell division stage on fruit quality and peel development of Zaomi Ponkan. The main aim of the research was to determine the optimum concentration of GA3 for Zaomi Ponkan for controlling fruit cracking. Moreover, the study also sought to delve into the physiological mechanisms through which GA3 regulates peel thickness and cell wall components, and reduces fruit cracking. [Methods] Zaomi Ponkan trees exhibiting good growth and consistency were selected. The experiment was conducted in favorable weather conditions starting at the cell division stage (21 and 28 days after flowering, DAF). The pre-prepared GA3 stock solution was diluted with water to achieve four concentrations: 0 (control, CK), 50, 100, and 200 mg·L-1.0.05% Tween-80 was added as an emulsifier to ensure effective absorption. The solutions were applied evenly on the entire trees, and each treatment included eight trees, using 16 L of the solution per treatment. The samplings were made at the key developmental stages: the late division stage (70 DAF), the late expansion stage (130 DAF), and the maturation stage (190 DAF). Over 100 fruits were measured using a vernier caliper to assess fruit maximum width each time. The collected samples were then analyzed in the laboratory for several parameters, including the fruit size, peel thickness and firmness at maturity stage and cracking rate. Particularly, the study observed the dynamic changes in the peel thickness and cell wall composition of the fruits of the 100 mg·L-1 GA3 treatment during the period of 30-70 DAF. Using the paraffin sectioning techniques, the differences of cell size and quantity were examined, aiming to elucidate the anatomical reasons behind GA3-induced peel thickening. [Results] The results demonstrated that after treatment with 50, 100, and 200 mg·L-1 GA3, the fruit peel became noticeably rougher in the late division stage, although no significant external changes were noted in the late stage of expansion and the maturation stage. Interestingly, while GA3 applications did not alter the size or weight of the fruit across these developmental stages, a significant increase in peel thickness was observed. During the maturation stage, it was found that the fruit peel hardness of the fruits treated with 50, 100, and 200 mg·L-1 GA3 was slightly higher (5.38 N, 5.26 N, and 5.41 N, respectively) compared with the control (CK, 4.71 N), though not significantly. Furthermore, the three concentrations of GA3 significantly reduced the fruit cracking rate. Compared with the 19.91% fruit cracking rate of the CK, the fruit cracking rates decreased to 10.72%, 8.06%, and 8.70% for the 50, 100, and 200 mg·L-1 GA3 treatments, respectively. The fruits of Zaomi Ponkan treated with 100 mg·L-1 GA3 at 21 and 28 DAF, were observed from 30 to 70 DAF. The results showed that at 40 DAF, GA3 treatment significantly promoted thickening of the peel, with the peel thickness treated with 100 mg·L-1 GA3 reaching 3.53 mm, an increase of about 5.7% compared with the CK (3.34 mm). By 60 DAF, the peel thickness reached its maximum value both in the GA3 treatments and the CK. However, by 70 DAF, although the peel thickness in both sharply decreased, the peel thickness in the GA3 treatments remained greater than that of the CK. The paraffin section analysis was further used to investigate the physiological and anatomical reasons for the peel thickening caused by GA3 at 40 DAF. The results showed that the number of cells in a unit area (1 mm×1 mm) of the epicarp and albedo did not significantly differ between the 100 mg·L-1 GA3 treatment and the CK. However, the GA3 treatment significantly increased the number of cell layers (162.9 layers) compared with the CK (151.5 layers). Throughout the observation period, the content of hemicellulose in the peel showed an increasing trend, while the lignin content displayed a decreasing trend. However, after the application of 100 mg·L-1 GA3, the overall content of both hemicellulose and lignin in the peel increased. [Conclusion] Applying different concentrations of GA3 during the cell division stage could effectively promote the peel thickening, increase the content of the hemicellulose and lignin, and ultimately reduce the cracking rate of the Zaomi Ponkan fruits, and 100 mg·L-1 GA3 treatment obtained the higher prevention effect. Detailed analysis revealed that GA3-induced peel thickening resulted from the enhanced cell layers. Additionally, GA3 also led to an increase in hemicellulose and lignin content. The increase in the peel thickness and the rise in the hemicellulose and lignin content might be important factors in preventing fruit cracking.